Hasil Belajar Myob (Mind Your Own Business) Ditinjau Dari Pemahaman Pengantar Akuntansi Dan Bahasa Inggris Pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2012/2013 - NOBERTI, SUWENTI, Drs. Sudarto HS., MM (2017)
The purpose of this study was to determine: 1) the influence of Introductory Understanding of Accounting on MYOB (Mind Your Own Business) Learning Achievement, 2) the influence of English on MYOB (Mind Your Own Business) Learning Achievement, 3) the influence of the Introductory Understanding of Accounting and English on on MYOB (Mind Your Own Business) Learning Achievement. Associative Quantitative methods used. Inroads in this research were 100 students with a sample of 80 students were taken by purposive sampling technique in a simple way, which has been adjusted to predetermined criteria. The data collection technique using a questionnaire that has been tested with the validity and reliability. Data analysis technique used is student value data. Results of regression analysis regression equation Y = 3,808 + 0,618 (X1) + 0,434 (X2), which means the MYOB (Mind Your Own Business) learning achievement is influenced by the introductory understanding of accounting and English. Based on the analysis and discussion can be concluded that: (1) the introductory understanding of accounting is a significant effect on MYOB (Mind Your Own Business) learning achievement. It is evident from the regression analysis obtained a value> is 6,306 > 1,991 with significant value 0.00 <0.05. (2) English significantly to MYOB (Mind Your Own Business) learning achievement. It is evident from the regression analysis obtained a value> is 4,610 > 1,991 with 0.000 significance value <0.05. (3) the introductory understanding of accounting and English together have a significant effect on student achievement. It is evident from the regression analysis obtained a value> is 60,030 > 3,115 with 0.000 significance value <0.05. (4) variable introductory understanding of accounting and English a major influence together amounting 60,9% while 30,1% were due to other factors